Intelligences in Strategic Issues Management: Challenging the Mutually Beneficial Relationships Paradigm - Bowen, Shannon A.; Health, Robert L. (PARTECIPAZIONE E CONFLITTO, 2020)
Mutually beneficial relationships (MBRs), a concept used to conceptualize public relations processes and outcomes, has been featured relatively uncritically for many years. This normative concept became an elixir for collective problem solving and shared decision making. Careful consideration of highly contested issues reveals evidence that within-group MBRs can prevent overarching solutions, decisions between issue groups, and can constitute stalemating or hegemonic tribalism. Strategic issues management (SIM) provides decision-making intelligences by which conflict between businesses and other members of society can be understood and resolved. Issue advocates’ adversarial strategies can frustrate any society’s ability to solve problems and make meaningful decisions, even when parties share a common motivating value. Stalemated public policy interpretations create sores that cannot heal; complex problems cannot be solved. Thus, MBRs are not the promised panacea or even a normative approach. Within-group MBRs can prevent between-group MBRs. An ethically engaged and rhetorically astute SIM process offers a constructive alternative to understanding complex, contested issues and offering informed problem resolution. Relationships do not have to be mutually beneficial to be included within the realm of public relations. In fact, relationships can span a continuum while still warranting and requiring the attentions, expertise, and activities of public relations. As long as ethical standards are maintained, those relationships can exist in whatever form is most intelligent for the handling of issues. In that view, public relations truly joins strategic management.